Academic Affairs Strategic Plan, 2009-2014 - Academic Affairs (Sonoma State University)
Following the WASC 2008 visit and the prior work of the University Planning Steering Committee, the Division of Academic Affairs moved to update its Strategic Plan. The update is intended to reflect the strategic goals for academics developed in the draft University Strategic Plan and much of the content of continuing relevance of the document titled "Long Range Academic Plan." (The latter document was developed by the Senate's Academic Planning Committee.) The work of updating the Academic Affairs Strategic Plan was carried out by the Joint Committee for Academic Planning (JCAP), which consists of the Deans Council and the members of the Senate Academic Planning Committee. The plan was formally endorsed by the Academic Planning Committee and recommended to the Academic Senate, which concurred in endorsing it in April 23, 2009. Based on these endorsements, the Provost adopted it for the Division of Academic Affairs in April 27, 2009.